2009
DOI: 10.1016/j.ydbio.2008.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Unique organization of the frontonasal ectodermal zone in birds and mammals

Abstract: The faces of birds and mammals exhibit remarkable morphologic diversity, but how variation arises is not well-understood. We have previously demonstrated that a region of facial ectoderm, which we named the Frontonasal Ectodermal Zone (FEZ), regulates proximo-distal extension and dorso-ventral polarity of the upper jaw in birds. In this work, we examined the equivalent ectoderm in murine embryos and determined that the FEZ is conserved in mice. However, our results revealed that fundamental differences in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
127
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(134 citation statements)
references
References 48 publications
4
127
0
3
Order By: Relevance
“…Although a number of pathways, such as bone morphogenetic protein (BMP), fibroblast growth factor (FGF) and Wingless (WNT) (Brugmann et al, 2007), may contribute to differential growth, SHH plays a crucial role in dorsoventral patterning, midline width variation, anterior outgrowth and palatal fusion (Marcucio et al, 2005;Hu and Marcucio, 2009;Young et al, 2010). When we compared embryonic stages corresponding to the period of maximal shape convergence, we found that Shh expression was localized to the distal tip and margins of the frontonasal, maxillary and primitive oral cavity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although a number of pathways, such as bone morphogenetic protein (BMP), fibroblast growth factor (FGF) and Wingless (WNT) (Brugmann et al, 2007), may contribute to differential growth, SHH plays a crucial role in dorsoventral patterning, midline width variation, anterior outgrowth and palatal fusion (Marcucio et al, 2005;Hu and Marcucio, 2009;Young et al, 2010). When we compared embryonic stages corresponding to the period of maximal shape convergence, we found that Shh expression was localized to the distal tip and margins of the frontonasal, maxillary and primitive oral cavity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The frontonasal ectodermal zone is one important signaling center that regulates the morphogenesis of the upper jaw. [25][26] This signaling center, defined by the boundary between Fgf8 and Shh expression in the FNP surface ectoderm, can induce expression of Bmp2, Bmp4 and Bmp7 in the underlying mesenchyme. Bmps are known to regulate the growth of facial primordia, 26 with Bmp2-and Bmp4-regulating speciesspecific upper jaw patterning in birds.…”
Section: Resultsmentioning
confidence: 99%
“…[25][26] This signaling center, defined by the boundary between Fgf8 and Shh expression in the FNP surface ectoderm, can induce expression of Bmp2, Bmp4 and Bmp7 in the underlying mesenchyme. Bmps are known to regulate the growth of facial primordia, 26 with Bmp2-and Bmp4-regulating speciesspecific upper jaw patterning in birds. 43 Using whole-mount in situ hybridization, we determined that the expression patterns of Fgf8, Bmp2 and Bmp4 were similar in wild-type and yautja embryos ( Figure 5B and data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Orofacial clefting may also arise from defective BA1 development, because clefting of both palate (24,25) and lip (26,27) can derive from deficient growth of the maxillary component of BA1. Defects of midline formation, on the other hand, arise from the failure of proper patterning or signaling from the prechordal plate and ventral forebrain (28,29) and the frontonasal ectodermal zone, which direct the formation of the midline of the face (30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%